Performance and impact of contact tracing in the Sudan virus outbreak in Uganda, September 2022-January 2023 - Mercy Wendy Wanyana; Rebecca Akunzirwe; Patrick King; Immaculate Atuhaire; Robert Zavuga; Bernard Lubwama; Zainah Kabami; Sherry Rita Ahirirwe; Mackline Ninsiima; Hellen Nelly Naiga; Jane Frances Zalwango; Marie Gorreti Zalwango; et al. (International Journal of Infectious Diseases, 2024)
Background: Contact tracing (CT) is critical for ebolavirus outbreak response. Ideally, all new cases after the index case should be previously-known contacts (PKC) before their onset, and spend minimal time ill in the community. We assessed the impact of CT during the 2022 Sudan Virus Disease (SVD) outbreak in Uganda. Methods: We collated anonymized data from the SVD case and contacts database to obtain and analyze data on CT performance indicators, comparing confirmed cases that were PKC and were not PKC (NPKC) before onset. We assessed the effect of being PKC on the number of people infected using Poisson regression. Results: There were 3844 contacts of 142 confirmed cases (mean: 22 contacts/case). Forty-seven (33%) confirmed cases were PKC. PKCs had fewer median days from onset to isolation (4 vs 6; P<0.007) and laboratory confirmation (4 vs 7; P<0.001) than NPKC. Being a PKC vs NPKC reduced risk of transmitting infection by 84% (IRR=0.16, 95% CI 0.08-0.32). Conclusion: Contact identification was sub-optimal during the outbreak. However, CT reduced the time SVD cases spent in the community before isolation and the number of persons infected in Uganda. Approaches to improve contact tracing, especially contact listing, may improve control in future outbreaks.